Pelatihan Pengelolaan Keuangan Keluarga Di Masa Pandemi pada Karyawan Tidak Tetap di Fakultas Ekonomi Unesa - Susi Handayani; Hariyati Hariyati; Eni Wuryani; Mariana Mariana; Insyirah Putikadea (Universitas Negeri Surabaya, 2020)
The Covid-19 pandemic has impacted to almost all levels of society, including non-permanent staff named Tenaga Kependidikan Tidak Tetap (TKTT) and cleaning staff at Faculty of Economics Unesa. As an effort to help the economic conditions of non-permanent staffs family at Faculty of Economics Unesa, it is necessary to have community service activities that can reduce their burden and provide knowledge about financial management on family during this pandemic. The activities are about distributing daily needs stuffs and financial management training during the Covid-19 pandemic. Knowledge and understanding of financial management are very important as the key to solve financial problems during this pandemic. The aim of this activity is expected the non-permanent staff at Faculty of Economics can make their financial well plan and well manage to improve their welfare on future and happiness of their families. Financial management training has been held offline by adhering to World Health Organisation (WHO)s health protocols during the Covid-19 pandemic. The results of the activity show that the participants are excited because they get new knowledge on how to manage their financial and being able to distinguish between needs and wants on their lifestyle.